Characterization Study of PVDF/ Cloisite Hollow Fiber Membrane in Aqueous Diethanolamine - Rosmawati, Naim; Sureena, Abdullah; N., Zulkifli (Penerbit Universiti Teknologi Malaysia, 2016)
Different concentrations of PVDF/Cloisite hollow fiber membranes were prepared and studied via immersion test. The differences in membrane properties were observed by immersion tests at 10 days, 20 days and 30 days in DEA solution. The membranes were characterized via liquid entry pressure (LEPW) and contact angle. Surface morphology analysis study was conducted before and after immersion test using scanning electron microscopy. From the result obtained, the liquid entry pressure and contact angle showed decreasing effect after immersion in DEA solution for 30 days. SEM analysis indicated that increasing DEA concentration creates more finger-like structure compared to pristine membrane. Incorporation of cloisite into PVDF membranes improves the contact angle value but development of more finger-like structure is subjected to wetting problem.